Respiratory health of children exposed to PM10: consequence of construction waste open dumping - Jeevanaraj, Pravina; Munianddey, Samala; Hashim, Zailina (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
Introduction: Due to rapid urbanization, Malaysia is currently undergoing extensive amount of construction activities and significant rise in the construction waste. Improper construction wastes management practices have led to rise in the waste open dumping sites which may significantly affect the environment and public health. This study was undertaken to assess air pollution in such a site and the impact to the respiratory health of children studying in a nearby school. Methods: A comparative cross-sectional study was conducted in Sungai Buloh (exposed) and Kuala Selangor (comparative). Concentration of PM10 was monitored at the open dumping site (n=15), a nearby primary school (n=45) and a comparative primary school (n=12). Parents who gave consent (n=229) answered a questionnaire related to child’s respiratory health whereas their children participated in lung function assessment. Results: Concentration of PM10 at the dumping site, exposed school and comparative school was 0.245±0.048mg/m3, 0.270±0.020mg/m3 and 0.051±0.016mg/m3 respectively, with the first two significantly exceeded the 24-hour Malaysian Air Quality Standard (MAQS) for PM10 (0.150mg/m3). Besides, PM10 concentration in the exposed school was similar to the dumping site (p>0.05) and many folds higher than the comparative school (p<0.001). There was a significant risk of cough (PR=1.55), phlegm (PR=1.70), wheezing (PR=1.55) and obstructive pattern of lung function defect (PR male = 4.36; PR female = 3.65) among the exposed group children than their comparative counterpart. Conclusion: Open dumping of construction waste would release substantial amount of PM10 into ambient air and ultimately affect the respiratory health of community, especially children.